Differentiation expression of toll‐like receptor4 (TLR4) caused by the dysregulation of microRNA‐140‐5p is responsible for the development of postoperation infection. Issue 3 (15th October 2018) - Zheng, Ge; Li, Zhishu; Xiang, Wenna; Huang, Yumao; Pan, Minli
Abstract: Background: Toll‐like receptor4 (TLR4) has proven to be an important factor that's responsible for the development of postoperation infection. MicroRNAs (miRNAs) are widely regarded as key mediators of gene expression. The objectives of our study were to identify miRNA(s) and the target genes differentially expressed in monocytes in the individuals with postoperation infection. Methods: MiRNA microarrays were performed to identify and compare miRNA expression in monocytes from those with or without postoperative infection. In‐silico analysis was used to further investigate the target miRNAs and finally, luciferase assay and real‐time polymerase chain reaction (PCR) were performed to confirm the target miRNA identified. Enzyme‐linked immunosorbent assay, real‐time PCR and Western‐blot were performed to explore the role of miR‐140 involved in postoperation infection. Results: MiRNA microarray results showed that ten miRNAs were upregulated in the postoperation infection group, while six miRNAs were downregulated, compared with those in the postoperation group without infection. Computational analysis was further performed to reveal that four miRNAs (miR‐140, miR‐7, miR‐448, and miR‐217) targeted the 3′‐untranslated region (UTR) of TLR4 mRNA. The luciferase assay showed that only miR‐140 inhibited luciferase activity of wild‐type TLR4 3′‐UTR and the luciferase activity of the cells cotransfected with miR‐7, miR‐448 or miR‐217 and wild‐type or mutant TLR4 3′‐UTR was comparable with the control. Furthermore, only miR‐140 levels were significantly lower in the postoperation infection group, while levels of miR‐217, miR‐7, and miR‐448 showed no obvious difference between the postoperation infection and postoperation without infection groups. TLR4, tumor necrosis factor‐α (TNF‐α), and IL‐6 levels were much higher in the postoperation infection group. In comparison with the control group, TLR4, TNF‐α and Interleukin 6 (IL‐6) levels in cells were decreased following transfection with miR‐140 mimics and TLR4 small interfering RNA. However, the cells treated with lipopolysaccharides increased TLR4, TNF‐α, and IL‐6 levels. Conclusion: This study demonstrates that miR‐140 is differentially expressed in monocytes collected from patients diagnosed with postoperation infection. The downregulation of miR‐140 cause upregulation of toll‐like receptor4 (TLR4), a proinflammatory factor, and is associated with infection risk in patients received surgery. Abstract : This study demonstrates that miR‐140 is differentially expressed in monocytes collected from patients diagnosed with postoperation infection. The downregulation of miR‐140 cause upregulation of TLR4, a proinflammatory factor, and is associated with infection risk in patients received surgery.